A comprehensive perspective for exploring the trade-offs and synergies between carbon sequestration and grain supply in China based on the production possibility frontier. (20th June 2022) - Yang, Yixuan; Zhang, Shiqin; Xia, Fan; Yang, Yixuan; Li, Dehuan; Sun, Wei; Wang, Yuan; Xie, Yujing
Abstract: The growth of grain supply (GS) is generally achieved through production intensification, cropland expansion, or both, which have significant direct or indirect effects on carbon sequestration (CS). However, the comprehensive benefits of the two ecosystem services (ESs), determined by biophysical constraints and management conditions in specific regions, have not yet been thoroughly explored. In this study, the dynamic benefits of the two ESs was quantified by production possibility frontier (PPF) considering the biophysical constraints and management conditions in China during the years 2000–2015. An evaluation matrix combined with spatial analysis method was used to examine the spatiotemporal variations of the ES relationship, and a multiple logistic regression model was adopted to investigate the influencing mechanism that shape ES relationship. The results demonstrated that the ES relationship had considerable spatial heterogeneities in China, and synergy and trade-off were the dominant relationships during the study period. The further trade-off analyses of PPFs suggested that the fitting curve shape was concave trade-off type in 2000, backward S-type in 2005, and to a pattern between inverted backward S-type trade-off and convex trade-off type in 2015. Meanwhile, the threshold of the total benefits of the two ESs, which determines the influence degree that GS brings to bear on CS, decreased from 0.36 to approximately 0.07 kg/m 2 in 2000–2015. Cropland area, topography, soil texture, soil organic carbon, and chemical fertilizer use were important factors influencing the synergy and trade-off of ESs. This study provides a comprehensive perspective to explore the spatial-temporal dynamic characteristics and the influencing mechanism of ES relationship. Our findings could serve as a basis for the multi-objective optimal management of ESs, considering both biophysical constraints and management conditions. Graphical abstract: Image 1 Highlights: A framework was established to study relationship of the two ESs in municipal units. The ES relationship in more than 90% cities were synergies or trade-offs. The fitting curve shape of PPF was changed during 2000–2015. The benefits of the two ESs had an ever-reduced threshold during 2000–2015. Geographical and social factors affected the synergy and trade-off of the two ESs.